Pesantren's Historical Contribution to Indonesian Islamic Civilization and National Education System in the 4.0 Era - Ningrum, Elsa Setia (Sekolah Tinggi Agama Islam Kuningan, 2025)
Backround: This article analyzes the historical contribution of Islamic boarding schools (pesantren) to Indonesian Islamic civilization and their integration into the national education system in the era of the Industrial Revolution 4.0.Objective: This study aims to analyze the historical contribution of pesantren to Indonesian Islamic civilization, examine their role within the national education system, and explore the transformation of pesantren in responding to the challenges of the digital era 4.0.Method: Using a qualitative, descriptive-analytical design, data were collected through in-depth interviews, participatory observation, and documentation in selected pesantren that integrate religious and general education and have begun adopting digital learning. Data were reduced, categorized into thematic clusters, displayed in matrices and conceptual diagrams, and then interpreted through continuous verification.Findings and Implications: The findings show that pesantren function as relatively autonomous socio-educational systems that have historically preserved and localized the Islamic scholarly tradition while producing cadres of ulama, community leaders, and national figures. In the contemporary period, pesantren are increasingly integrated into the national education system through legal recognition, curriculum harmonization, and the implementation of internal quality assurance, positioning them as strategic partners of the state in character education and religious moderation. At the same time, pesantren are undergoing curriculum transformation, gradual technology integration, and strengthening of digital literacy while maintaining the classical traditions of sorogan-bandongan and dormitory life.Conclusion: The study proposes a three-dimensional model of pesantren contribution historical-civilizational, systemic-policy, and pedagogic-digital as a framework for reading the continuity and innovation of pesantren in the 4.0 era.